2008
DOI: 10.1007/s12011-008-8102-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Levels of Dietary Silicon on Bone Development of Growing Rats and Turkeys Fed Semi-purified Diets

Abstract: Two experiments were conducted using a completely randomized design to study the effects of high levels of silicon (Si) supplementation on bone development, structure, and strength in growing rats and turkeys. Rats were supplemented at two dietary Si levels: 0 and 500 ppm; and the turkeys were supplemented at four dietary Si levels: 0, 135, 270, and 540 ppm in semi-purified diets of dextrose-albumin for rats and dextrose-casein for turkeys. The experiments lasted 8 and 4 weeks for the rats and turkeys, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
2
13
1
Order By: Relevance
“…Although positive in vivo effects of silicon supplementation on bone formation and connective tissue metabolism were reported in earlier studies 27 , other studies have reported no effects 9 . It has also been reported that silicon supplementation of tetraethylorthosilicate in rats and turkeys resulted in lower bone size and strength parameters such as those measured by maximal load and elasticity of the femur and tibia bone but these conclusions were based on numerical rather than statistically significant differences 35 . These contradictory data highlight the importance of providing a form of silicon in the diet that not only remains bioavailable but will not undergo negative interactions with other minerals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although positive in vivo effects of silicon supplementation on bone formation and connective tissue metabolism were reported in earlier studies 27 , other studies have reported no effects 9 . It has also been reported that silicon supplementation of tetraethylorthosilicate in rats and turkeys resulted in lower bone size and strength parameters such as those measured by maximal load and elasticity of the femur and tibia bone but these conclusions were based on numerical rather than statistically significant differences 35 . These contradictory data highlight the importance of providing a form of silicon in the diet that not only remains bioavailable but will not undergo negative interactions with other minerals.…”
Section: Discussionmentioning
confidence: 99%
“…The Expert group on Vitamins and Minerals (EVM) 37 set a Safe Upper Level for daily consumption of silicon at 700 mg silicon/day for adults over a lifetime (equivalent to 12 mg silicon/kg body weight/day for a 60 kg adult). Preliminary data indicating safe upper limits for oral ingestion of silicon in poultry have been determined using turkeys 35 but ensuring proposed supplement levels are safe and comply with required labelling standards 38 will still need to be considered before marketing this product for use in poultry or humans. Whilst this communication has focused on the potential use of bioavailable silicon in poultry, there are many other spheres of animal production, human health and high performance sport where a bioavailable form of silicon may also be highly beneficial in maintaining and potentially repairing skeletal integrity.…”
Section: Discussionmentioning
confidence: 99%
“…There may also be an effect on collagen that improves bone strength independent of mineral density [46]. In contrast to studies reporting improved bone strength, two experimental studies in rats have reported small reductions in bone strength when excessively high and prolonged levels of dietary silicon were added to the diet [43, 47]. This may represent an antagonistic effect of excessive silicon that decreases intestinal absorption of calcium and magnesium when very high amounts of silicon are provided in the diet [47].…”
Section: Silicon's Role In Bone Formationmentioning
confidence: 99%
“…20–50 mg Si/day, are considered as unlikely to cause adverse effects in humans with normal renal function . By contrast, two studies in rats and turkeys have reported deleterious effects on bone development attributed to an antagonistic relation of Si at high levels with calcium and magnesium . Therefore, in the present study, the epithelium integrity loosening, assessed by a decrease in the TEER values following OSA–VC incubation at the highest nonphysiological concentration, could be explained by the antagonistic effect of excessive Si with calcium that is necessary to ensure the tight junction integrity.…”
Section: Discussionmentioning
confidence: 51%